2017
DOI: 10.1111/camh.12208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical change after the implementation of the Choice and Partnership Approach within an Australian Child and Adolescent Mental Health Service

Abstract: Background: The Choice and Partnership Approach (CAPA) model has been implemented widely into Child and Adolescent Mental Health Services (CAMHS) in the United Kingdom and similar health systems in Australia and New Zealand. This study investigated whether the implementation of the CAPA model was related to changes in client clinical outcomes and response times within a regional Australian CAMHS. Method: Multiple measures of time, clinical diagnosis, contact and outcomes were collected at intake and discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…The partnership approach is explained to new families during the initial Choice appointment and families have the option to participate in services delivered according to this approach or receive mental health care under the traditional model. Most studies (Clark et al , 2018; Naughton et al , 2015, 2018) reported significant reductions in wait time for the first appointment, and Fuggle et al (2016) found a trend of shorter wait times and increase in the overall number of first appointments offered. Wilson et al (2015) found that the eight agencies met demand with available appointments and had no waitlist, despite an increase in demand over the study period.…”
Section: Resultsmentioning
confidence: 99%
“…The partnership approach is explained to new families during the initial Choice appointment and families have the option to participate in services delivered according to this approach or receive mental health care under the traditional model. Most studies (Clark et al , 2018; Naughton et al , 2015, 2018) reported significant reductions in wait time for the first appointment, and Fuggle et al (2016) found a trend of shorter wait times and increase in the overall number of first appointments offered. Wilson et al (2015) found that the eight agencies met demand with available appointments and had no waitlist, despite an increase in demand over the study period.…”
Section: Resultsmentioning
confidence: 99%
“…In our review, only seven evaluations reported clinical outcomes, all reporting positive findings. 14 30 31 36 41 64 66 However, only three measured changes from baseline. 14 31 36 Patient-reported outcome measures, such as the Revised Children’s Anxiety and Depression Scales or Goal Based Outcome Tool, while recommended by healthcare systems internationally and demonstrated to benefit shared decision-making, 91 were not often reported.…”
Section: Discussionmentioning
confidence: 99%
“…Yet some viewed it as compromising effectiveness and one service user was demotivated by limited sessions. Although some studies suggest that focused interventions are inappropriate for complex cases, others indicate that goal‐focused systems can improve efficiency without reducing clinical effectiveness or user satisfaction (Fuggle et al, 2016; Naughton et al, 2018; Robotham et al, 2010). Taken together, this highlights the importance of monitoring clinical outcomes and user satisfaction.…”
Section: Discussionmentioning
confidence: 99%